Characterization of the Mechanical Behavior of Magnesia Spinel Refractories Using Image Correlation. Issue 6 (27th August 2014) - Belrhiti, Younes; Huger, Marc; Chotard, Thierry; Pop, Octavian; Germaneau, Arnaud; Doumalin, Pascal; Dupré, Jean Christophe
<x xml:space="preserve">Abstract</x> The improvement in thermal shock resistance of refractory materials is among the crucial properties that interest researchers and industrials. The "flexibility" in terms of large strain‐to‐rupture is, up to now, an important parameter to develop such characteristic. This can be obtained by generating a network of microcracks within the microstructure of the material under mechanical solicitations. As an outcome, the mechanical behavior can vary from fragile to a large nonlinear one depending on the degree of microcracking present inside the material. In fact, this nonlinear behavior of ceramics related to their microstructure is behind the possibility to enhance the level of strain‐to‐rupture for a better accommodation to the high level of strain induced by thermal shock solicitations. This study is devoted to apply digital imaging correlation method to support mechanical behavior analysis for the evaluation of the thermal shock ability of refractory materials. In this paper, mechanical characterization of magnesia spinel materials has been carried out using different experimental tests. These nonlinear materials are characterized by a mechanical behavior strongly dependent on their microstructure.